Single-Mode Semiconductor Nanowire Lasers With Coupled Cavities - Ullah, Salman; Pian, Sijie; Dai, Fang; Wang, Yilun; Ma, Yaoguang; Yang, Qing (Frontiers in Chemistry, 2021)
Semiconductor nanowires are one of the most fascinating topics over the past few decades. As miniaturized coherent light sources, semiconductor nanowires have been attracting tremendous attention in recent years for scientific and technological interest as potential ultra-compact, low cost, high efficiency, and low power consumption. Among different types of lasers, one-dimensional nanowires are of great interest as a promising material for next-generation nanophotonics and nanoelectronics applications due to their unique optical and electrical properties. Semiconductor nanowire lasers with single-mode output are vital in a variety of practical applications ranging from signal processing, spectroscopy, displays, optical sensing, on-chip communications, and biological studies. This article reviews the basic technology and research progress of single-mode semiconductor nanowire lasers. Afterward, the key methods and development of the different types of coupling to achieved single-mode laser output are elaborated. Finally, the challenges faced by each scheme are summarized.